A study to investigate the intra-rater and inter-rater reliability of goniometric measurements of dart throwers motion of asymptomatic wrists. (June 2016) - Cliff, Nicola J; Rust, Philippa A
Introduction: This study investigated the intra-rater and inter-rater reliability of measuring dart throwers motion of asymptomatic wrists with a handheld manual goniometer typical of that used in the clinical setting. Method: Working in pairs, each rater took three repeated measures of radial extension and of ulnar flexion of both wrists using a goniometer positioned on the radiodorsal aspect of the radius proximally and the second metacarpal distally. Both raters and subjects were blinded, and measurements were read by an independent observer. Subjects were of varied age, gender and with no history of wrist pathology. Subjects rated how difficult they found the dart throwers motion to perform using a 5-point Likert scale. Results: Measurements were collected from both wrists of 37 subjects (74 wrists). The intraclass correlation coefficient for intra-rater measurements of radial extension was 0.89 (95% CI 0.86–0.92) and for ulnar flexion was 0.92 (95% CI 0.90–0.94). Standard deviation for radial extension was 4.2° and for ulnar flexion 3.6°. The intraclass correlation coefficient for inter-rater measurements of radial extension was 0.83 (95% CI 0.74–0.89) and for ulnar flexion was 0.81 (95% CI 0.72–0.88). Subjects rated the movement more difficult to perform with the non-dominant side (P=0.006), and standard deviation was greater when the subject found dart throwers motion difficult to perform. No significant associations were found (P<0.05) to suggest that reliability is influenced by hand dominance, gender, age, level of perceived difficulty or data collection site. Discussion: Our study confirms good reliability when using this method to measure dart throwers motion. It is suggested that dart throwers motion can be measured to compare different subjects and monitor change; however, studies need to be undertaken with a symptomatic population.